Implementasi Least Squares Support Vector Machine dan SMOTE untuk Klasifikasi Kesehatan Mental - Marcelino Marcelino; Muhammad Rizky Pribadi (STMIK Banjarbaru, 2026)
Mental health disorders such as depression, anxiety, and stress are global problems that require accurate early detection. This study proposes a mental health classification model using machine learning algorithms based on data from the Depression Anxiety Stress Scales (DASS-42) questionnaire and respondent demographic features. The main method used is Least Squares Support Vector Machine (LSSVM) combined with Synthetic Minority Oversampling Technique (SMOTE) and Backward Elimination feature selection. From testing on 39,775 respondent data, Backward Elimination successfully reduced more than 40% of the feature dimensions by selecting the most statistically significant attributes (p-value < 0.05). Oversampling with SMOTE proved successful in overcoming class imbalance in minority labels. Performance evaluation showed that LSSVM using the Radial Basis Function (RBF) kernel provided the most optimal results compared to the Linear and Polynomial kernels, with an F1-Score of 83.96% for Depression, 77.30% for Anxiety, and 82.00% for Stress. This proposed model contributes to the development of a more computational, efficient, and accurate mental health screening system.Keywords: Backward Elimination; DASS-42; LSSVM; Mental Health; SMOTE AbstrakGangguan kesehatan mental seperti depresi, kecemasan, dan stres merupakan masalah global yang memerlukan deteksi dini yang akurat. Penelitian ini mengusulkan model klasifikasi tingkat kesehatan mental menggunakan algoritma machine learning berdasarkan data kuesioner Depression Anxiety Stress Scales (DASS-42) dan fitur demografis responden. Metode utama yang digunakan adalah Least Squares Support Vector Machine (LSSVM) yang dikombinasikan dengan Synthetic Minority Oversampling Technique (SMOTE) dan seleksi fitur Backward Elimination. Dari pengujian terhadap 39.775 data responden, Backward Elimination berhasil mereduksi lebih dari 40% dimensi fitur dengan menyeleksi atribut yang paling signifikan secara statistik (p-value < 0.05). Oversampling dengan SMOTE terbukti berhasil mengatasi ketidakseimbangan kelas pada label minoritas. Evaluasi kinerja menunjukkan bahwa LSSVM menggunakan kernel Radial Basis Function (RBF) memberikan hasil paling optimal dibandingkan kernel Linear dan Polynomial, dengan pencapaian F1-Score sebesar 83.96% untuk Depresi, 77.30% untuk Kecemasan, dan 82.00% untuk Stres. Model yang diusulkan ini berkontribusi dalam pengembangan sistem screening kesehatan mental yang lebih komputasional, efisien, dan akurat.